Method for preparing 2, 5-furandimethanol through catalytic hydrogenation of 5-hydroxymethylfurfural

By using ZrCu bimetallic catalyst and appropriate reaction conditions, the HMF selective hydrogenation problem was solved, and the effect of efficient preparation of 2,5-furandimethyl alcohol was achieved, and the generation of by-products was avoided.

CN119504671AActive Publication Date: 2025-02-25FUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411668488.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently convert 5-hydroxymethylfurfural (HMF) into 2,5-furandimethyl alcohol (BHMF) through non-precious metal catalysts, and excessive hydrogenation is prone to occur to form by-products.

Method used

Using ZrCu bimetallic catalyst, selective hydrogenation of HMF is achieved by adjusting the addition amount of NaBH4 and the reaction conditions, and high-efficiency 2,5-furandimethanol is prepared.

Benefits of technology

Efficient selective hydrogenation of HMF was achieved, with a yield of 97.2%. By adjusting the active site and acid-base strength of the catalyst, the reaction efficiency was improved and the generation of by-products was avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504671A_ABST
    Figure CN119504671A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing 2, 5-furandimethanol through catalytic hydrogenation of 5-hydroxymethylfurfural, and belongs to the technical field of fine chemical engineering. According to the method, a bimetallic catalyst is prepared by reducing a bimetallic aqueous solution through sodium borohydride, then 5-hydroxymethylfurfural, the bimetallic catalyst and isopropanol are added into a reaction kettle and subjected to a closed reaction for 1-5 h at the temperature of 100-140 DEG C at the stirring speed of 500 rpm, the reaction product 2, 5-furandimethanol is obtained, the highest conversion rate of 5-hydroxymethylfurfural reaches 99.4%, and the highest conversion rate of 2, 5-furandimethanol reaches 99.4%. The highest yield of the 2, 5-furandimethanol is up to 97.2%. The catalyst is extremely simple in preparation method and low in cost, and a catalytic system is green and efficient and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fine chemicals, and specifically relates to a method for preparing 2,5-furan dimethanol by catalytic hydrogenation of 5-hydroxymethylfurfural. Background Art

[0002] Biomass is widely distributed in nature and has abundant reserves. It is an environmentally friendly, clean and renewable resource. It has important practical significance for alleviating the shortage of fossil fuel resources and environmental pollution. In recent years, the conversion of biomass resources into platform chemicals has attracted widespread attention from researchers. Among these platform compounds, 5-hydroxymethylfurfural (HMF) is considered to be one of the most important biomass-based platform molecules and is widely used in the preparation of multifunctional compounds such as fine chemicals, key pharmaceutical intermediates, functional polyesters, solvents and liquid fuels. A variety of high-value-added chemicals such as 2,5-furan dimethanol (BHMF) and 2,5-dimethylfuran (DMF) can be synthesized through chemical reactions such as oxidation and hydrogenation. Among these compounds, 2,5-furan dimethanol, as a widely used chemical intermediate and fuel precursor, has unique advantages in improving the performance of traditional polyesters and synthesizing green and degradable bio-based polyester new materials. It also has huge market potential in the production of resins, polymers, artificial fibers and crown ethers. However, only a few studies have focused on the selective hydrogenation of HMF to prepare BHMF, mainly because HMF is easily over-hydrogenated to DMF and 2,5-dimethyltetrahydrofuran (DMTHF) in the presence of noble metals and H2. Therefore, it is particularly important to develop a green, economical and efficient non-noble metal catalyst to achieve preferential hydrogenation of the aldehyde group on the HMF molecule and avoid hydrogenation of the hydroxymethyl group on another carbon position and C=C hydrogenation on the furan ring as much as possible. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing 2,5-furan dimethanol by catalytic hydrogenation of 5-hydroxymethylfurfural.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing 2,5-furan dimethanol by catalytic hydrogenation of 5-hydroxymethyl furfural: 5-hydroxymethyl furfural, a ZrCu bimetallic catalyst and isopropanol are added into a closed reactor, reacted at 100-140°C for 1-5h at a stirring rate of 500rpm, and then cooled to room temperature to obtain the 2,5-furan dimethanol.

[0005] The preparation method of the above ZrCu bimetallic catalyst comprises the following steps: (1) Dissolve the bimetallic salt in deionized water, referred to as solution A; separately dissolve sodium borohydride in deionized water, referred to as solution B; (2) Use a dropper to slowly add solution B into solution A. After all the solution is added and the bubbles are released, stir manually until a uniformly mixed colloid is obtained. (3) The colloid is aged, dried, ground and sieved to obtain the ZrCu bimetallic catalyst.

[0006] Furthermore, the mass ratio of the above-mentioned isopropanol, 5-hydroxymethylfurfural and ZrCu bimetallic catalyst is 99:1:(0.25-1.5).

[0007] Furthermore, the concentration of the sodium borohydride is 5 mol / L.

[0008] Furthermore, the mass ratio of the zirconium oxychloride, copper nitrate and sodium borohydride is 2.4:1.8:0.38-1.14.

[0009] Furthermore, the aging time is 1 hour, and the drying temperature is 80°C.

[0010] The beneficial effects of the present invention are: (1) The present invention can adjust the active sites and acid-base strength of the catalyst by adjusting the amount of NaBH4 added; and by adjusting the reaction conditions, a higher yield of 2,5-furan dimethanol can be prepared.

[0011] (2) In the bimetallic catalyst prepared by the present invention, the strong synergistic effect between the two metals Cu-Zr plays an important role in the reaction pathway of catalytic hydrogenation of 5-hydroxymethylfurfural to prepare 2,5-furan dimethanol.

[0012] (3) The non-precious metal catalyst prepared by the present invention has low cost, simple preparation method, mild reaction conditions, high economy and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 : XRD patterns of the catalysts prepared in Examples 2-6, 8 and 10.

[0014] Figure 2 : SEM images of the catalysts prepared in Example 2 and Example 4. DETAILED DESCRIPTION

[0015] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0016] The preparation method of the catalyst in the following embodiments comprises: Weigh a certain amount of metal precursor and dissolve it in 10mL of deionized water under the assistance of ultrasound, which is recorded as solution A. Take another certain amount of sodium borohydride and dissolve it in deionized water under the assistance of ultrasound to make its concentration 5mol / L, which is recorded as solution B. After the ultrasound is over, use a dropper to slowly add solution B to solution A. After all the drops are added and the bubbles are released, stir manually until a uniformly mixed colloid is obtained. After that, place it for 1 hour, put the aged medicine into an oven, and dry it at 80°C overnight. Then grind the dried product in a mortar and pass it through an 80-120 mesh sieve to obtain the bimetallic catalyst, which is named ZrCuO x -y, where "y" represents the amount of sodium borohydride solution added.

[0017] Example 1 ZrCuO x -0 2.4 g ZrOCl2·8H2O and 1.8 g Cu(NO3)2·3H2O were accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. After that, the aged product was placed in an oven and dried at 80°C overnight. The dried product was then ground in a mortar and passed through a 80-120 mesh sieve to obtain the bimetallic catalyst ZrCuO x -0.

[0018] Example 2 ZrCuO x -2 2.4g ZrOCl2·8H2O and 1.8g Cu(NO3)2·3H2O were accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 0.38g NaBH4 was also accurately weighed and dissolved in 2 mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight, and then the dried product was ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrCuO x -2.

[0019] Example 3 ZrCuO x -3 2.4g ZrOCl2·8H2O and 1.8g Cu(NO3)2·3H2O were accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 0.57g NaBH4 was also accurately weighed and dissolved in 3 mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight, and then the dried product was ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrCuO x -3.

[0020] Example 4 ZrCuO x -4 2.4g ZrOCl2·8H2O and 1.8g Cu(NO3)2·3H2O were accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 0.76g NaBH4 was also accurately weighed and dissolved in 4 mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight, and then the dried product was ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrCuO x -4.

[0021] Example 5 ZrCuO x -5 2.4g ZrOCl2·8H2O and 1.8g Cu(NO3)2·3H2O were accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 0.95g NaBH4 was also accurately weighed and dissolved in 5 mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight, and then the dried product was ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrCuO x -5.

[0022] Example 6 ZrCuO x -6 2.4g ZrOCl2·8H2O and 1.8g Cu(NO3)2·3H2O were accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 1.14g NaBH4 was also accurately weighed and dissolved in 6 mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight, and then the dried product was ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrCuO x -6.

[0023] The XRD patterns of the bimetallic catalysts prepared in Examples 2-6 are as follows: Figure 1 As shown, the bimetallic catalyst ZrCuO was reduced by regulating sodium borohydride x -y The diffraction peaks at 31.5°, 44.4°, 49.7° and 56.6° correspond to the (102), (103), (013) and (302) crystal planes of ZrO2 (PDF#97-017-3963), respectively, indicating that these catalysts exhibit diffraction peaks similar to those of single metal ZrOx-4, all of which belong to the orthorhombic system. After the introduction of Cu species, new diffraction peaks appeared in the XRD spectrum. The diffraction peaks at 17.6°, 28.9° and 31.8° correspond to the (100), (-111) and (111) crystal planes of ZrO2 (PDF#97-024-8445), respectively. The diffraction peaks at 38.8° and 38.9° correspond to the (111) and (200) crystal planes of CuO (PDF#97-029-1387), respectively, both of which belong to the monoclinic system. This indicates that the introduction of Cu species changes the crystal form selection of ZrO2, and different amounts of sodium borohydride solution added have a significant effect on the formation of catalyst species and crystal forms. With the increase in the amount of sodium borohydride solution, the monoclinic ZrO2 will gradually transform into the orthorhombic system. The ratio of orthorhombic and monoclinic systems in the XRD spectrum increases, the preferred orientation of the crystal form changes, and the diffraction peak of CuO gradually weakens, indicating that it is gradually reduced to dispersed Cu2O and Cu. From the XRD spectrum of the best catalyst CuZrOx-4, it can be seen that the two strongest diffraction peaks belong to the orthorhombic and monoclinic systems of ZrO2, respectively, and their ratio is close to 1. CuO (111) and (200) crystal planes exist at the same time, which verifies the successful synthesis of the Zr-Cu bimetallic catalyst.

[0024] After adding 0.2g 5-hydroxymethylfurfural, 0.2g bimetallic catalyst and 19.8g isopropanol to a stainless steel autoclave, the autoclave is sealed. After high-purity nitrogen is introduced to replace the air in the autoclave 3-4 times, the closed autoclave is stirred at a speed of 500rpm, heated to 120°C and maintained for 2h, and the reaction is terminated and cooled naturally to room temperature. After the experiment, the reaction mixture is centrifuged, the supernatant is taken, and standard solutions such as 5-hydroxymethylfurfural and 2,5-furan dimethanol are prepared, and quantitative analysis is performed using a gas chromatograph, and qualitative analysis is performed using a gas chromatograph-mass spectrometer. The test results of Examples 1-6 are listed in Table 1.

[0025] The effect of sodium borohydride dosage on catalyst activity was investigated. As shown in Table 1, under the conditions of 120 °C, 2h and 500rpm, when no sodium borohydride solution was added, the reaction products were dispersed and the yield of 2,5-furan dimethanol was extremely low. With the increase of sodium borohydride dosage, the conversion rate of 5-hydroxymethylfurfural and the selectivity of 2,5-furan dimethanol both showed a trend of first increasing and then decreasing. The best effect was achieved when the sodium borohydride solution dosage was 4mL, the conversion rate of 5-hydroxymethylfurfural was 99.4%, and the yield of 2,5-furan dimethanol increased to 97.2%; when the sodium borohydride solution dosage was 2mL, the conversion rate of 5-hydroxymethylfurfural and the yield of 2,5-furan dimethanol were both low, but its selectivity reached 88.3%, which may be due to the fact that the amount of sodium borohydride was too small, insufficient to form ZrO2 in the catalyst preparation, and insufficient Cu reduction, resulting in insufficient catalyst activity. When the amount of sodium borohydride solution was increased to 6 mL, the conversion rate and yield dropped significantly. This may be due to the reduction of CuO to Cu2O and Cu under the condition of excessive sodium borohydride. The active sites of the catalyst mainly come from ZrO2 and CuO. By adjusting the amount of sodium borohydride, the content and interaction of ZrO2 and CuO in the catalyst can be controlled, thereby adjusting the active sites of the catalyst, indicating that the amount of sodium borohydride has a very important influence on the activity of the catalyst. Therefore, the optimal amount of sodium borohydride solution is 4 ml.

[0026] Table 1 Catalytic results of Examples 1-6 Example 7 ZrCuO x -4 2.4g ZrOCl2·8H2O and 1.8g Cu(NO3)2·3H2O were accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 0.76g NaBH4 was also accurately weighed and dissolved in 4mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight. The dried product was then ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrCuO x -4.

[0027] Example 8 ZrO x -4 2.4 g ZrOCl2·8H2O was accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 0.76 g NaBH4 was also accurately weighed and dissolved in 4 mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight. The dried product was then ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrO x -4.

[0028] Example 9 ZrO x -2 2.4 g ZrOCl2·8H2O was accurately weighed and dissolved in 10 mL deionized water under the assistance of ultrasound, which was recorded as solution A. 0.38 g NaBH4 was also accurately weighed and dissolved in 2 mL deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, and the aged product was placed in an oven and dried at 80°C overnight. The dried product was then ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named ZrO x -2.

[0029] Example 10 CuO x -4 1.8 g Cu(NO3)2·3H2O was accurately weighed and dissolved in 10 mL of deionized water under the assistance of ultrasound, which was recorded as solution A. 0.76 g NaBH4 was also accurately weighed and dissolved in 4 mL of deionized water under the assistance of ultrasound, which was recorded as solution B. After the ultrasound was completed, solution B was slowly added to solution A with a dropper. After all the drops were added and the bubbles were released, it was manually stirred until a uniformly mixed colloid was obtained. After that, it was placed for 1 hour, the aged product was placed in an oven, and dried at 80°C overnight, and then the dried product was ground in a mortar and passed through an 80-120 mesh sieve to obtain the bimetallic catalyst, which was named CuO x -4.

[0030] Example 11 CuO x -2 Accurately weigh 1.8g Cu(NO3)2·3H2O, dissolve it in 10 mL of deionized water under the assistance of ultrasound, and record it as solution A. Accurately weigh 0.38g NaBH4, dissolve it in 2mL of deionized water under the assistance of ultrasound, and record it as solution B. After the ultrasound is over, use a dropper to slowly add solution B to solution A. After all the drops are added and the bubbles are released, stir manually until a uniformly mixed colloid is obtained. After that, place it for 1 hour, put the aged product in an oven, and dry it at 80°C overnight. Then grind the dried product in a mortar and pass it through an 80-120 mesh sieve to obtain the bimetallic catalyst, which is named CuO x -2.

[0031] Example 12 ZrNiO x -4 Accurately weigh 2.4g ZrOCl2·8H2O and 1.8g Ni(NO3)2·6H2O, dissolve in 10 mL deionized water with the assistance of ultrasound, and record it as solution A. Accurately weigh 0.76g NaBH4, dissolve in 4mL deionized water with the assistance of ultrasound, and record it as solution B. After the ultrasound is finished, use a dropper to slowly add solution B to solution A. After all the drops are added and the bubbles are released, stir manually until a uniformly mixed colloid is obtained. After that, place it for 1 hour, put the aged medicine into an oven, and dry it at 80°C overnight. Then grind the dried product in a mortar, pass through an 80-120 mesh sieve to obtain the bimetallic catalyst, which is named ZrNiO x -4.

[0032] Example 13 ZrCoO x -4 Accurately weigh 2.4g ZrOCl2·8H2O and 1.8g Co(NO3)2·6H2O, dissolve in 10 mL deionized water with the assistance of ultrasound, and record it as solution A. Accurately weigh 0.76g NaBH4, dissolve in 4mL deionized water with the assistance of ultrasound, and record it as solution B. After the ultrasound is finished, use a dropper to slowly add solution B to solution A. After all the drops are added and the bubbles are released, stir manually until a uniformly mixed colloid is obtained. After that, place it for 1 hour, put the aged medicine into an oven, and dry it at 80°C overnight. Then grind the dried product in a mortar, pass through an 80-120 mesh sieve to obtain the bimetallic catalyst, which is named ZrCoO x -4.

[0033] The XRD patterns of catalysts 8 and 10 are shown in Figure 2. Figure 1 As shown in the figure, the diffraction peaks of the monometallic catalyst ZrOx-4 at 31.5°, 44.4°, 49.7° and 56.6° correspond to the (102), (103), (013) and (302) crystal planes of ZrO2 (PDF#97-017-3963), respectively, indicating that the main component of the catalyst is ZrO2, which belongs to the orthorhombic system. The diffraction peaks of the monometallic catalyst CuOx-4 at 36.5°, 43.3° and 50.4° correspond to the 111 crystal plane of Cu2O (PDF#97-002-6963) and the (111) and (200) crystal planes of Cu (PDF#97-004-3493), respectively, indicating that the main components of the catalyst are Cu2O and Cu, both of which belong to the monoclinic system. This characterization result shows that when the amount of sodium borohydride solution added is 4 mL, a large amount of monoclinic ZrO2 can be effectively synthesized in the catalyst prepared by single metal Zr, while single metal Cu will be further reduced due to excessive sodium borohydride, and more crystal characteristics of Cu2O and Cu will be shown in the XRD spectrum. Therefore, controlling the amount of sodium borohydride solution added has an important influence on the catalytic activity of the catalyst.

[0034] 0.2g 5-hydroxymethylfurfural, 0.2g bimetallic catalyst and 19.8g isopropanol were added to a stainless steel autoclave and the autoclave was sealed. After high-purity nitrogen was introduced to replace the air in the autoclave 3-4 times, the air was stirred at 500rpm in the closed autoclave, heated to 120°C and maintained for 2h, and the reaction was terminated and cooled naturally to room temperature. After the experiment, the reaction mixture was centrifuged, the supernatant was taken, and standard solutions of 5-hydroxymethylfurfural, 2,5-furan dimethanol, etc. were prepared. The quantitative analysis was performed using a gas chromatograph, and the qualitative analysis was performed using a gas chromatograph-mass spectrometer. The test results are listed in Table 2.

[0035] The effect of metal components on catalytic activity was investigated. It can be seen from Table 2 that at 120 °C, 2 h and 500 rpm, when only single metal Zr or Cu was used to prepare the catalyst, both showed lower 5-hydroxymethylfurfural conversion and 2,5-furan dimethanol yield. The amount of sodium borohydride was also very important. When the amount of sodium borohydride solution was 2 mL, ZrO x -2 is basically ineffective, while CuO x -2 has a lower effect. When the amount of sodium borohydride solution is 4mL, the effects of the two are just the opposite, which can be clearly seen from the SEM ( Figure 2 ), which may be that the excess sodium borohydride is sufficient to form flaky zirconium oxide, but CuO is over-reduced to Cu2O and Cu, causing a large number of Cu species to aggregate and lose activity. When a bimetallic catalyst prepared with Zr and Cu showed a higher yield than a single metal and its physical mixture, up to 97.2%, which also shows that there is a good synergistic effect between the two metals Cu-Zr. Usually in the process of HMF hydrogenation to BHMF, Cu-based catalysts usually require higher temperatures than Ni-based and Co-based catalysts. Therefore, the corresponding ZrNiO x -4 and ZrCoO x- 4. It can be found that under the same conditions, both catalysts show a certain transfer hydrogenation effect, but neither is as good as ZrCuO x The effect of -4 further proves that the two metals have a strong synergistic effect at a lower temperature. Therefore, Zr-Cu bimetallic catalysts have obvious advantages over single metal catalysts.

[0036] Table 2 Catalytic results of Examples 7-13 Embodiment 14 Add 0.2 g 5-hydroxymethylfurfural, 0.2 g ZrCuO x -4 catalyst and 19.8g isopropanol, and then the reactor is sealed. After high-purity nitrogen is introduced to replace the air in the reactor 3-4 times, the closed reactor is stirred at a speed of 500rpm, heated to 100, 110, 120, 130, and 140℃ respectively and maintained for 2h, and the reaction is terminated and naturally cooled to room temperature. After the experiment, the reaction mixture is centrifuged, the supernatant is taken, and standard solutions such as 5-hydroxymethylfurfural and 2,5-furan dimethanol are prepared, and quantitative analysis is performed using a gas chromatograph, and qualitative analysis is performed using a gas chromatograph-mass spectrometer. The test results are listed in Table 3.

[0037] The effect of reaction temperature on catalytic activity was investigated. As shown in Table 3, under the conditions of 100 °C, 2 h and 500 rpm, the conversion rate of 5-hydroxymethylfurfural was 83.6%, and the yield of 2,5-furan dimethanol was 82.4%; under the conditions of 140 °C, 2 h and 500 rpm, the conversion rate of 5-hydroxymethylfurfural was 99.9%, and the yield of 2,5-furan dimethanol was 76.8%; and under the conditions of 120 °C, 2 h and 500 rpm, the conversion rate of 5-hydroxymethylfurfural was 99.4%, and the yield of 2,5-furan dimethanol increased to 97.2%. This shows that high temperature conditions are conducive to the conversion of 5-hydroxymethylfurfural, but when the temperature is too high, it will lead to the production of more by-products and the selectivity of 2,5-furan dimethanol will decrease. Therefore, the appropriate reaction temperature can obtain higher 2,5-furan dimethanol, and the optimal reaction temperature is 120 °C.

[0038] Table 3 Effect of reaction temperature on catalytic activity Embodiment 15 Add 0.2 g 5-hydroxymethylfurfural, 0.2 g ZrCuO x -4 catalyst and 19.8g isopropanol, and then the reactor is sealed. After high-purity nitrogen is introduced to replace the air in the reactor 3-4 times, the closed reactor is stirred at a speed of 500rpm, heated to 120°C and maintained for 1, 2, 3, 4, and 5 hours respectively, and the reaction is terminated and naturally cooled to room temperature. After the experiment, the reaction mixture is centrifuged, the supernatant is taken, and standard solutions such as 5-hydroxymethylfurfural and 2,5-furan dimethanol are prepared, and quantitative analysis is performed using a gas chromatograph, and qualitative analysis is performed using a gas chromatograph-mass spectrometer. The test results are listed in Table 4.

[0039] The effect of reaction time on catalytic activity was investigated. As shown in Table 4, under the conditions of 120 ℃, 1 h and 500 rpm, the conversion rate of 5-hydroxymethylfurfural was 93.6%, and the yield of 2,5-furan dimethanol was 86.4%; while under the conditions of 120 ℃, 2 h and 500 rpm, the conversion rate of 5-hydroxymethylfurfural was 99.4%, and the yield of 2,5-furan dimethanol increased to 97.2%. When the reaction time was increased to 5 h, the conversion rate remained almost unchanged, but the yield gradually decreased. This may be due to the occurrence of other side reactions caused by the long reaction time, which led to a decrease in the yield of 2,5-furan dimethanol. Therefore, the optimal reaction time is 2 h.

[0040] Table 4 Effect of reaction time on catalytic activity Example 16 0.2 g 5-hydroxymethylfurfural, 19.8 g isopropanol and 0.05, 0.1, 0.15, 0.2, 0.25 and 0.3 g ZrCuO were added to a stainless steel autoclave. x -4 catalyst and then sealed the reactor. After high-purity nitrogen was introduced to replace the air in the reactor 3-4 times, the reactor was stirred at a speed of 500 rpm, heated to 120 ° C and maintained for 2 hours respectively, and the reaction was terminated and naturally cooled to room temperature. After the experiment, the reaction mixture was centrifuged, the supernatant was taken, and standard solutions of 5-hydroxymethylfurfural, 2,5-furan dimethanol, etc. were prepared. Gas chromatograph was used for quantitative analysis, and gas chromatography-mass spectrometry was used for qualitative analysis. The test results are listed in Table 5.

[0041] The effect of catalyst dosage on catalytic activity was investigated. As shown in Table 5, under the conditions of 120 ℃, 2h and 500rpm, when the catalyst dosage was 0.05g, the conversion rate of 5-hydroxymethylfurfural was 73.6%, and the yield of 2,5-furan dimethanol was 66.4%; while under the conditions of 120 ℃, 2h and 500rpm, when the catalyst dosage was 0.2g, the conversion rate of 5-hydroxymethylfurfural increased to 99.4%, and the yield of 2,5-furan dimethanol increased to 97.2%. When the catalyst dosage increased to 0.3g, the conversion rate remained almost unchanged, but the yield gradually decreased. This may be because the excessive amount of catalyst provided more catalytic active sites, and the by-products in the reaction system continued to increase, resulting in a decrease in the yield of 2,5-furan dimethanol. Therefore, the optimal catalyst dosage is 0.2g.

[0042] Table 5 Effect of catalyst dosage on catalytic activity As shown in Tables 1-5, a higher yield of 2,5-furan dimethanol (97.2%) can be obtained by adjusting the metal composition, the amount of sodium borohydride solution, the reaction temperature, the reaction time and the amount of catalyst.

[0043] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing 2,5-furan dimethanol by catalytic hydrogenation of 5-hydroxymethylfurfural, characterized in that: 5-Hydroxymethylfurfural, ZrCu bimetallic catalyst and isopropanol are added into a closed reactor, reacted at 100-140° C. for 1-5 hours at a stirring rate of 500 rpm, and then cooled to room temperature to obtain the 2,5-furan dimethanol.

2. The method according to claim 1, characterized in that: The preparation method of the ZrCu bimetallic catalyst comprises the following steps: (1) Dissolve a bimetallic salt in deionized water, referred to as solution A; separately dissolve sodium borohydride in deionized water, referred to as solution B; (2) Slowly add solution B into solution A using a dropper. After all solution B is added and the bubbles are released, stir manually until a uniformly mixed colloid is obtained. (3) The colloid is aged, dried, ground and sieved to obtain the ZrCu bimetallic catalyst.

3. The method according to claim 1, characterized in that: The mass ratio of the isopropanol, 5-hydroxymethylfurfural and ZrCu bimetallic catalyst is 99:1:(0.25-1.5).

4. The method according to claim 2, characterized in that: The concentration of sodium borohydride in step (1) is 5 mol / L.

5. The method according to claim 2, characterized in that: The mass ratio of the zirconium oxychloride, copper nitrate and sodium borohydride is 2.4:1.8:0.38-1.

14.

6. The method according to claim 2, characterized in that: The aging time is 1 hour, and the drying temperature is 80°C.

Citation Information

Patent Citations

  • Efficient composition for promoting solid hydrate, preparation method and method for intensifying generation of hydrates

    CN113817519A

  • Method for preparing dimethylfuran by catalyzing 5-hydroxymethylfurfural with Cu-based catalyst

    CN115974819A

  • Metal monatomic doped copper-based catalyst as well as preparation method and application thereof

    CN117019148A

  • Efficient method for preparing 2,5-dimethylfuran

    US20110263880A1